Fiddling while Rome burns? Conducting research with healthcare staff when the NHS is in crisis. Issue 1 (30th January 2020) - Sheard, Laura; Peacock, Rosemary
Abstract : Purpose: Health research in the UK is being impeded by a stretched NHS system. The purpose of this paper is to use the Great Fire of Rome as an allegory to understand the difficulties encountered by health researchers when attempting to conduct research within a healthcare system that is currently in crisis. Design/methodology/approach: The paper draws on both the authors' own and other research teams' experiences from the published literature in order to demonstrate that this difficulty is a widespread problem for the health research community in the UK. Findings: Recruitment and engagement issues across different research studies and clinical environments are often ascribed as being related to individual contexts or settings. Rather, the authors propose that these problems are actually writ large across nearly the entire NHS. The authors offer ideas for what can be done to alleviate the worst of this situation – a change in culture and ways of working alongside employing more pragmatic, rapid methods to engage exceptionally busy healthcare staff. Originality/value: The paper offers a provocative viewpoint that instead of seeking to individualise recruitment and engagement issues in relation to the local context, the research community should publicly acknowledge the universality of this problem in order to bring about meaningful change.